British headquarters (Sir Guy Carleton) papers, 1747 (1777)-1783 - Dorchester, Guy Carleton, Baron, 1724-1808; Washington, George, 1732-1799 (Photographed by Microfilming service, Recordak Corp., 1957)
These papers consist chiefly of the correspondence of Sir Guy Carleton although volumes 1-34 contain copies of letters received and sent by the previous commanders-in-chief. Included in the collection are 69 letters of George Washington concerning the New York campaign around Albany and Saratoga.